FISHGLOB_data: An integrated dataset of fish biodiversity sampled with scientific bottom-trawl surveys - Maureaud, A.A.; Palacios-Abrantes, J.; Kitchel, Z.; Mannocci, L.; Pinsky, M.L.; Fredston, A.; Beukhof, E.; Forrest, D.L.; Frelat, Romain; Palomares, M.L.D.; Pecuchet, L.; Thorson, J.T.; et al. (Springer, 2024)
Scientific bottom-trawl surveys are ecological observation programs conducted along continental shelves and slopes of seas and oceans that sample marine communities associated with the seafloor. These surveys report taxa occurrence, abundance and/or weight in space and time, and contribute to fisheries management as well as population and biodiversity research. Bottom-trawl surveys are conducted all over the world and represent a unique opportunity to understand ocean biogeography, macroecology, and global change. However, combining these data together for cross-ecosystem analyses remains challenging. Here, we present an integrated dataset of 29 publicly available bottom-trawl surveys conducted in national waters of 18 countries that are standardized and pre-processed, covering a total of 2,170 sampled fish taxa and 216,548 hauls collected from 1963 to 2021. We describe the processing steps to create the dataset, flags, and standardization methods that we developed to assist users in conducting spatio-temporal analyses with stable regional survey footprints. The aim of this dataset is to support research, marine conservation, and management in the context of global change.